Review of maintenance management for roads at the district level - Fortin, Stephanie Anne E.; Vergara, Angeline S.
Highway maintenance in the Philippines is conducted by DPWH for national roads. For this study the current practice of maintenance was documented. This was compared to the good management practice as suggested by the UK Road Liaison Group through gap analysis. The implementability of the DPWH manual at district level was examined and additional suggestions, where applicable, were forwarded. Documentation were gathered by conducting surveys and key informant interviews at DPWH District Offices and at the Bureau of Maintenance (BOM). The issues that were usually encountered by DPWH personnel were concerning the weather. Work in the field was affected depending on the weather condition. Overall, the implementability of the manual was 88.23%. This result implies that the practices of the maintenance sections still has to improve to conform on the existing manual. The gap analysis comparing the DPWH. manual to the suggested maintenance practice scored 71.25%. This rating could be further improved following some recommendations as follows: improving and maintaining an organized database, putting more attention on heavy-traffic zones for urban districts, and continually going for Long Term Performance Based Contracts.